A Study of the Factor Analysis on the Change in the Title of the Sponsorship of Chinese Professional Football Clubs. Issue 12 (2nd September 2018) - Lin, Jianjun; Dai, Jinjin; Li, Deyi
Abstract: Many Chinese professional football clubs change their names more frequently compared with professional football clubs outside of China. By analyzing the historical data of football development history, the title of the sponsorship of professional football clubs in China, as well as the change of property rights, and adopting the method of documentation and browsing method of portals and internet platforms such as the official website of Chinese Football Association, Baibu baike, and Netease CSL data live system, the titles of sponsorship of professional football clubs in China are changed frequently with significant club clustering. Many clubs even have fixed titles but have changed them along with the change in sponsors. The change in a football club title shall be triggered by factors such as the change of economic factors, the change in institutional factors and the combined action of economic factors and institutional factors together. However, the fundamental reason for the frequent change of clubs' titles shall be the undefined property structures of most clubs, as well as the issues of club brand values and property right confirmation.